Singularity-free finite element model of bone through automated voxel-based reconstruction. Issue 3 (17th February 2016) - Esposito, L.; Bifulco, P.; Gargiulo, P.; Fraldi, M.
Abstract : Computed tomography (CT) provides both anatomical and density information about tissues. Bone is segmented by raw images and Finite Element Method (FEM) voxel-based meshing technique is achieved by matching each CT voxel to a single finite element (FE). As a consequence of the automated model reconstruction, unstable elements – i.e. elements insufficiently anchored to the whole model and thus potentially involved in partial rigid body motion – can be generated, a crucial problem in obtaining consistent FE models, hindering mechanical analyses. Through the classification of instabilities on topological connections between elements, a numerical procedure is proposed in order to avoid unconstrained models.